Platelet-Oriented Inhibition in New TIA and Minor Ischemic Stroke (POINT) Trial: Rationale and design. Issue 6 (August 2013) - Johnston, S. Claiborne; Easton, J. Donald; Farrant, Mary; Barsan, William; Battenhouse, Holly; Conwit, Robin; Dillon, Catherine; Elm, Jordan; Lindblad, Anne; Morgenstern, Lewis; Poisson, Sharon N.; Palesch, Yuko
Background: Ischemic stroke and other vascular outcomes occur in 10–20% of patients in the three-months following a transient ischemic attack or minor ischemic stroke, and many are disabling. The highest risk period for these outcomes is the early hours and days immediately following the ischemic event. Aspirin is the most common antithrombotic treatment used for these patients. Aim: The aim of POINT is to determine whether clopidogrel plus aspirin taken <12 h after transient ischemic attack or minor ischemic stroke symptom onset is more effective in preventing major ischemic vascular events at 90 days in the high-risk, and acceptably safe, compared with aspirin alone. Design: POINT is a prospective, randomized, double-blind, multicenter trial in patients with transient ischemic attack or minor ischemic stroke. Subjects are randomized to clopidogrel (600 mg loading dose followed by 75 mg/day) or matching placebo, and all will receive open-label aspirin 50–325 mg/day, with a dose of 162 mg daily for five-days followed by 81 mg daily strongly recommended. Study Outcomes: The primary efficacy outcome is the composite of new ischemic vascular events — ischemic stroke, myocardial infarction, or ischemic vascular death — by 90 days. The primary safety outcome is major hemorrhage, which includes symptomatic intracranial hemorrhage. Discussion: Aspirin is the most common antithrombotic given to patients with a stroke or transient ischemic attack, as it reduces the risk of subsequent stroke. This trial expects to determine whether more aggressive antithrombotic therapy with clopidogrel plus aspirin, initiated acutely, is more effective than aspirin alone.